2016
DOI: 10.1016/j.cub.2016.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin Ring Formation and Tension Generation in Eukaryotic Cytokinesis

Abstract: Cell division facilitated by a contractile ring is an almost universal feature across all branches of cellular life, with the notable exception of higher plants. In all organisms that use a contractile ring for cell division, the process of cytokinesis can be divided into four distinct stages. Firstly, the cell needs to specify a location at which to place the cell division ring to ensure proper separation of the cell contents into two daughter cells. Secondly, the cell needs to be able to transport all the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 166 publications
1
110
0
3
Order By: Relevance
“…We also showed for the first time that PC12 cells with myosin IIB knockdown had a higher proliferative activity than myosin IIA knockdown or control cells. It has been reported that cytokinesis is facilitated by the constriction of a cortical ring made up of myosin II and actin filaments in animal and fungal cells (Cheffings et al, 2016; Zambon et al, 2017). Actomyosin-drived cellular contractility is recognized as an important promoter for increased tumor number, growth and progression (Samuel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed for the first time that PC12 cells with myosin IIB knockdown had a higher proliferative activity than myosin IIA knockdown or control cells. It has been reported that cytokinesis is facilitated by the constriction of a cortical ring made up of myosin II and actin filaments in animal and fungal cells (Cheffings et al, 2016; Zambon et al, 2017). Actomyosin-drived cellular contractility is recognized as an important promoter for increased tumor number, growth and progression (Samuel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to follow fluorescent proteins in live cells has been one of the most powerful tools for uncovering the mechanism of cytokinesis in model systems (34). To study the dynamics of individual proteins during the cell cycle, we developed a low-fluorescence culture medium that supports cell growth.…”
Section: Giardia Uses a Tubulin Reservoir To Support Rapid Mitosis Anmentioning
confidence: 99%
“…SummaryCytokinesis depends on a contractile actomyosin ring in many eukaryotes [1, 2, 3]. Myosin II is a key component of the actomyosin ring, although whether it functions as a motor or as an actin cross-linker to exert its essential role is disputed [1, 4, 5].…”
mentioning
confidence: 99%